Therapeutic eﬀects of a novel venom abstract (ZK002) solution in an alkali-burned corneal wound-healing model - Peng, Wen-Yan; Wang, Fei; Yang, Shuang-Jian; Sun, Qin-Yan; Zhou, Heng-Shen; Li, Xiaoyi; Jiang, Zheng-Xuan; Zhou, Shi-You (Molecular vision, 2023)
Corneal alkali burns can progress to corneal epithelial defects, inflammation, scarring, and angiogenesis, potentially leading to blindness. Therefore, we examined the therapeutic effects of a novel ophthalmic solution (ZK002) on wound healing in alkali-burned rat corneas. In this study, we attempted to treat alkali-exposed rat corneas using topical application of either an ophthalmic solution with ZK002 or an anti-vascular endothelial growth factor agent for 14 days. We evaluated corneal edema, corneal neovascularization area, and histological changes. We also assessed the inflammatory (MMP-9, MMP-2, and interleukin-1β) and angiogenic (vascular endothelial growth factor receptor 2, VEGFR2) markers. Levels of inflammatory (matrix metalloproteinase (MMP)-9, MMP-2, and interleukin-1β), profibrotic (α-smooth muscle actin, α-SMA; transforming growth factor-β2,TGF-β2), and angiogenic (vascular endothelial growth factor-receptor 2, VEGFR2) factors, as well as peroxisome proliferator-activated receptor γ (PPARγ) mRNA expression, were measured. The analyses showed that alkali exposure caused an increase in corneal edema and fibrosis with corneal neovascularization. The accumulation of α-smooth muscle actin-positive myofibroblasts and the deposition of transforming growth factor-β2 on the alkali-exposed corneas were noted on day 14. The mRNA expression levels of interleukin-1β, MMP-9, MMP-2, VEGFR2, and profibrotic factors were decreased in the ZK002 group compared with the control group during the early period of corneal alkali burns on day 14. However, the expression level of PPARγ mRNA was increased in the ZK002 group. ZK002 decreased the fibrotic reaction and prevented neovascularization in the cornea after an alkali burn. Therefore, the novel ophthalmic solution ZK002 could be a potentially promising therapeutic clinical treatment for corneal wound healing.